2005
DOI: 10.1176/appi.ajp.162.6.1179
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Psychiatric Comorbidity on Recovery and Recurrence in Generalized Anxiety Disorder, Social Phobia, and Panic Disorder: A 12-Year Prospective Study

Abstract: Objective-The authors sought to observe the long-term clinical course of anxiety disorders over 12 years and to examine the influence of comorbid psychiatric disorders on recovery from or recurrence of panic disorder, generalized anxiety disorder, and social phobia.Method-Data were drawn from the Harvard/Brown Anxiety Disorders Research Program, a prospective, naturalistic, longitudinal, multicenter study of adults with a current or past history of anxiety disorders. Probabilities of recovery and recurrence we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
586
9
15

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 796 publications
(654 citation statements)
references
References 38 publications
(37 reference statements)
44
586
9
15
Order By: Relevance
“…Renewal is a robust effect both in the laboratory and in clinical settings (Mineka et al, 1999;Mystkowski et al, 2002). Furthermore, in a longitudinal study of the clinical course of anxiety disorders over 12 years, it was demonstrated that anxiety disorders have a largely chronic course with low recovery rates and high relapse rates (Bruce et al, 2005). This illustrates the need to target relapse rates in treatment; thus, the findings that FGF2 renders rats less susceptible to relapse are potentially clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Renewal is a robust effect both in the laboratory and in clinical settings (Mineka et al, 1999;Mystkowski et al, 2002). Furthermore, in a longitudinal study of the clinical course of anxiety disorders over 12 years, it was demonstrated that anxiety disorders have a largely chronic course with low recovery rates and high relapse rates (Bruce et al, 2005). This illustrates the need to target relapse rates in treatment; thus, the findings that FGF2 renders rats less susceptible to relapse are potentially clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…In Burlington, Vermont, some degree of illness fear was found in 18.2% of the population [19]. Phobic disorders are comorbid with other psychiatric conditions, particularly anxiety disorders [20]. There is also an increasing risk of the patient developing depression and substance abuse disorder [21].…”
Section: Discussionmentioning
confidence: 99%
“…In the 12-year follow-up in the Harvard/Brown Anxiety Disorders Research Program (HARP), only panic disorder had a favourable course, with 82 % achieving recovery, compared with 58 % for GAD, 48 % recovery for panic with agoraphobia and only 37 % for social phobia patients. The equivalent figures for recurrences during the follow-up period are 45 %, 58 % and 39 % respectively (Bruce et al 2005). Major depression is not included in the HARP data set.…”
Section: Coursementioning
confidence: 99%